Difficulties encountered by the grade ten township learners with respect to the concept of electricity - Dolo, Gilbert (University of the Western Cape, 2015)
Magister Educationis - MEd === The purpose of this study was to investigate the difficulties encountered by the grade ten township learners with respect to the concept of electricity. More specifically, the study attempted to explore the learners’ scientific knowledge by investigating their conceptions or alternative conceptions about electricity; the influence of learners’ age, career interests and gender issues on their conceptions of electricity and; the effectiveness of concept mapping (a pedagogic tool designed by Novak in the 1970s) in facilitating the learners’ understanding of electricity. The study was premised on socio-cultural constructivism as well as meaningful learning as espoused by Ausubel (1968).A Pre-Test-Post-Test Control Group Design was adopted in the study in which two comparable groups were used. The data was analyzed using both qualitative and quantitative research methods and the instruments that were used included a conception of electricity (COET) (originally adopted and administered in the Western Cape, Northern Cape provinces and in Norway in 1999 for the purpose of Science and Technology Literacy Project (STLP) with the hope that their reliability and validity was guaranteed); selected learner interviews and evaluation forms.The summary of findings has suggested that the Grade ten learners held misconceptions about the concept of electricity even after they were exposed to intervention that included concept mapping. In terms of the gender issues, there was no significant difference in performance between the boys and girls though the females outperformed their male counterparts at both groups. The underachievement of the older learners compared to the younger ones has also surfaced and that is against expectation since a number of studies carried out earlier (see Ogunniyi (1999)) have already corroborated such findings. With respect to career interests, what the learners indicated as their future dreams, i.e. what they intend to do and become, seems to have been influenced their performance at the pre- and post-test stages.